The effect of special exercises according to the physical biorhythm in the development of some bio-kinetic abilities and the accuracy of offensive punches for junior boxing - Al-Musawi, B. M. T.; Mohammed, M. J. (Annals of the Romanian Society for Cell Biology, 2021)
The purpose of this paper is to applying training types according to different stresses during the physical biorhythmic phase and during the positive and negative biorhythmic phases in developing some bio-kinetic abilities and offensive skills in boxing among juniors. And by noting the researcher being a boxing player, notices that there is a problem that most of the coaches organize their training units in the form of a single pace throughout the daily, weekly and monthly times, and they are not aware of the biorhythmic cycles and do not take into account the existence of such vital courses. As for the most important objectives, to identify the effect of special exercises according to the cycle of physical biorhythm to develop some bio-kinetic abilities and offensive skills of the young boxing players. The research community was represented in the Specialized School for Boxing in Wasit Governorate, affiliated to the Ministry of Youth and Sports, as the number of boxers in the junior category, aged (15-16) years, was (15) boxers. (5) boxers for the exploratory experiment and the sample was then divided into two control groups and a number of (5) boxers in each group and also intentionally, i.e. (33%) of the research community of the experimental group and (33%) of the research community of the control group, in order to take Boxers closest in their level of physical biorhythm. The researchers concluded that the training program, which was in terms of the physical biorhythm of each player, had a significant influence on the development of the experimental group at the expense of the control group, so all its variables appeared and were of significant significance and greater value compared to the post-tests of the control group, and therefore the training program had a significant influence on the development.